Design and Virtual Assembly Method of the Circulating Planetary Roller Screw Mechanism - Guan Qiao; Rong Liao; Shijie Guo; Nan Zhang; Geng Liu (Jixie chuandong)
The nut threadless area of the circulating planetary roller screw mechanism design method is proposed based on the specific structural characteristics of its nut， and related formulas are derived for the structural parameters of the nut threadless area. On this basis， a cross-section design method for rollers， screws， and nuts is developed in accordance with the actual meshing situation of the components. By adjusting the clearance between the two oblique edges and the arc， oblique edges， the meshing accuracy of the screw and roller threads， roller and nut threads can be improved. The relationship between the distance from the center of the rollers to the end of the cam ring is provided to ensure the meshing between the rollers and the screw， the rollers and the nut. Finally， according to the working principle and structural characteristics of the circulating planetary roller screw mechanism， a three-dimensional model is established using its relevant structural parameters， and the relevant assembly is carried out. The design and virtual assembly method of the nut threadless area proposed can serve as a model and guide for the design and analysis of the circulating planetary roller screw mechanism.